Impact of Integration of Self-Regulated Learning (SRL) and Phonic Approcah in Flipped Classroom Model on Reading Literacy Skills, Reading Strategies, and Reading Motivation - Nurmahanani, Indah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
A lack of practical strategies and appropriate media are obstacles for students to master early reading literacy skills and increase their reading interest. The purpose of this study was to investigate the integration of self-regulated learning and phonics approaches in the flipped classroom approach. The method used in this study was a quasi-experimental study involving 351 elementary school students from several schools. Participants were divided into three groups: Experiment 1 (SRL instruction-based teaching and phonics approach in the flipped classroom model), Experiment 2 (SRL instruction-based teaching in the flipped classroom model), and the control group (traditional teacher-centred teaching). The data analysis employed in this study included descriptive statistics and analysis of variance (ANOVA). The results showed that the integration of phonics approaches and self-regulated learning (SRL) instruction-based teaching in the flipped classroom model was able to improve reading literacy skills (vocabulary and text comprehension), the use of reading strategies, and psychological factors that support the development of reading skills such as self-efficacy, reading motivation and student autonomy. However, among all these principles, the principle of phonics and the SRL approach to teaching that has the most significant influence on reading ability and psychological factors of reading ability development is student autonomy. This study suggests that combining SRL instruction-based teaching with a phonics approach in the flipped classroom model can be an effective alternative for teachers to enhance students' language skills, including reading literacy.